Determination of adequate positive end‐expiratory pressure level required for carbon dioxide homeostasis in an animal model of infant laparoscopy. Issue 8 (19th May 2020) - Karlsson, Jacob; Fodor, Gergely H.; dos Santos Rocha, Andre; Lin, Na; Habre, Walid; Wallin, Mats; Hallbäck, Magnus; Peták, Ferenc; Lönnqvist, Per‐Arne
Abstract : Background: Capnoperitoneum provides a ventilatory challenge due to reduction in end‐expiratory lung volume and peritoneal carbon dioxide absorption in both children and adults. The primary aim of this controlled interventional trial was to determine the positive end‐expiratory pressure (PEEP) level needed to ensure for adequate carbon dioxide clearance and preservation of carbon dioxide homeostasis in an experimental model of infant laparoscopy. The secondary aim was to evaluate potential effects on cardiac output of PEEP and abdominal pressure level variations in the same setting. Methods: Eight chinchilla bastard rabbits were anesthetized and mechanically ventilated. Intra‐abdominal pressures were randomly set to 0, 6, and 12 mm Hg by carbon dioxide insufflation. Carbon dioxide clearance using volumetric capnography, arterial blood gas data, and cardiac output was recorded, while PEEP 3, 6, and 9 cmH2 O were applied in a random order. Results: A PEEP of 9 cmH2 O showed restoration of carbon dioxide clearance without causing changes in arterial partial pressure of carbon dioxide and bicarbonate and with no associated deterioration in cardiac output. Conclusion: The results promote a PEEP level of 9 cmH2 O in this model of infant capnoperitoneum to allow for adequate carbon dioxide removal with subsequent preservation of carbon dioxide homeostasis. The use of high PEEP was not associated with any decrease in cardiac output.